2015
DOI: 10.1245/s10434-015-4879-3
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Histone Lysine Demethylase JMJD3/KDM6B in Colorectal Cancer

Abstract: JMJD3 has prognostic significance in CRC and mediates p15INK4B expression. These results imply that elucidation of the JMJD3 role may lead to a new therapeutic approach for CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 34 publications
0
40
1
Order By: Relevance
“…JmjC domain-containing proteins function as important regulators of pluripotency and control differentiation of embryonic stem cells (19)(20)(21)(22). Several Jumonji proteins have been either implicated in the regulation of cancer progression or were suggested as a biomarker for several cancer types, like JMJD1A for gastric or JMJD3 for colorectal cancer (23,24).…”
mentioning
confidence: 99%
“…JmjC domain-containing proteins function as important regulators of pluripotency and control differentiation of embryonic stem cells (19)(20)(21)(22). Several Jumonji proteins have been either implicated in the regulation of cancer progression or were suggested as a biomarker for several cancer types, like JMJD1A for gastric or JMJD3 for colorectal cancer (23,24).…”
mentioning
confidence: 99%
“…This gene is essential for life after birth, as knockout mice are born smaller and die perinatally due to respiratory failure (21,61,62). Previous studies have pointed to a potential tumor-suppressive role of KDM6B in specific tissues (such as lung, colon, and pancreas) (30)(31)(32)63), while in others (such as blood, breast, and brain) it may play an opposite tumor-promoting function (24)(25)(26). This demethylase is an important player at the intersection between cellular senescence and cancer (22,29), and it also positively regulates epidermal differentiation (33).…”
Section: Discussionmentioning
confidence: 99%
“…The sphere-forming capability of various SCC cell lines in cell-cycle control, senescence, and differentiation, and may play a role in cancer development in a context-dependent manner (21)(22)(23). In fact, KDM6B expression is upregulated in several malignancies, such as Hodgkin's lymphoma (24), breast cancer (25), gliomas (26), melanoma (27), and renal cell carcinoma (28), while it is suppressed in others, including lung adenocarcinoma and squamous cell carcinoma (29), colon cancer (30,31), and liver and pancreatic cancers (32). While inactivating KDM6B gene mutations are only found in 1%-3% of SCCs (cBioPortal for Cancer Genomics; http:// www.cbioportal.org), the gene, like NOTCH1, has been implicated as a positive determinant of squamous cell differentiation (33).…”
Section: Introductionmentioning
confidence: 99%
“…PHF8 has been reported to be involved in several types of cancer, including breast cancer ( 7 ), non-small cell lung cancer (NSCLC) ( 8 ), acute promyelocytic leukemia ( 9 ) and esophageal squamous cell carcinoma ( 10 ). Previous studies have demonstrated that aberrant epigenetic alteration of histone lysine demethylation is crucial in the development of CRC ( 11 ). PHF2 and Jumonji-domain containing 3 (JMJD3) histone demethylase, a tumor suppressor, are downregulated in colon cancer ( 12 ).…”
Section: Introductionmentioning
confidence: 99%